Fatigue of mooring chain links subjected to out-of-plane bending: Experiments and modeling. (June 2019) - Mamiya, E.N.; Castro, F.C.; Ferreira, G.V.; Nunes Filho, E.L.S.A.; Canut, F.A.; Neves, R.S.; Malcher, L.
Abstract: This work presents an experimental apparatus for fatigue testing of chain links subjected to out-of-plane bending. The test consists of a pre-tensioned chain segment subjected to a cyclic transverse displacement of the middle link, resulting in out-of-plane bending of the adjacent links. Aiming to obtain new data for the evaluation of fatigue-life prediction methodologies, eight tests were designed considering different interlink angles and mean stress levels. The tests were conducted with positive interlink angles, a condition typically found in the fairlead/mooring chain system. A stress-based fatigue analysis using the Smith-Watson-Topper parameter yielded life estimates within factor-of-three boundaries. This very good correlation resulted from a combination of factors: a fatigue parameter that considers the mean stress effect, its calibration using test data from specimens with a surface condition similar to that of the chains, and a reasonable engineering estimate of the stress at the hotspot. Highlights: Experimental apparatus for fatigue testing of chain links under out-of-plane bending New experimental data with positive interlink angle Stress-based fatigue life estimates within factor-of-three boundaries. Conventional design rules may produce nonconservative life estimates.